The Method of Determining the Function of Traffic Costs for the Node with Unregulated Flows of Requests - N.А, Naumova (International Journal of Mathematical Research, 2013)
Modeling of transportation networks with the purpose of optimization is a vital problem. The difficulties of numerical solution of optimization problems for networks mainly depend on the analytical definition of the function of traffic costs. We provide a developed mathematical model of transportation network based on the generalized Erlang time distribution. We also propose a classification of nodes. For the case of the node with unregulated intersection of multichannel lines as a system of mass service, we obtain an analytical realization of the function of traffic costs. We describe a method of determining the parameters of the generalized Erlang law from experimental data.